Strategi Efektif Pengelolaan Keuangan bagi Mahasiswa Perantau - Luhendra, Subhan Karunia Irobi (Maliki Interdisciplinary Journal, 2025)
This study aims to examine various effective strategies in financial management for overseas students through a literature review approach. The problem of financial management in overseas students is an important issue considering the financial independence required when living away from parents. The method used is a systematic literature review by analysing scientific articles, journals, and publications related to student financial management published in the period 2019-2024. The results of the study showed several key strategies in the financial management of overseas students, including: (1) preparation of a realistic monthly budget, (2) separation of emergency funds, (3) utilisation of financial recording applications, and (4) implementation of a frugal lifestyle. The main challenges identified include limited income, fluctuating needs, and consumptive temptations. This study recommends the importance of financial literacy education since the beginning of college and the utilisation of technology to support more efficient financial management. The results of this study can be a reference for overseas students in optimising their financial management during the study period.